Dance Syntax and Possibility: Moving Beyond Structural Analysis - Miranda Medina, Juan Felipe (2023)
In this work we contend that studying dance syntax systematically is essential to gain a deeper understanding of dance practices. The reason is that syntax has to do with an essential aspect of dance, music and action in general, namely possibility. To the best of our knowledge, the efforts towards a systematic method to study dance syntax are scarce. Therefore, this work proposes the method of Finite-State Automata, borrowed from computer science, and presents three case studies of progressive complexity were the method is applied: (1) learning the basics of salsa, (2) diachronically comparing hip-pushing action in Afro-Ecuadorian Bomba del Chota, and (3) characterizing improvisation in Afro-Peruvian zapateo. While the first case is didactic and introduces the method progressively, the second and third cases are based on several years of fieldwork conducted by the authors with the Afro-Ecuadorian and Afro-Peruvian communities. The precondition for the application of the method we propose is structural analysis itself; that is, that the dance can be analyzed into small movement units that are combined progressively into more complex units. In regards to syntax, however, structural analysis is only the first step. The goal is a synthesis that brings forward the possibilities that arise from structural analysis; that is, the possibilities that are available to dancers and agents in a dance event. We trust that the approach to syntax this work presents will stimulate a renewed interest for researchers in dance, music and movement in general.